Extraction of Fatty Acids from Syzygium cumini Seeds with Different Solvents - KUMAR, A.; PADMANABHAN, N.; KRISHNAN, M.R.V. (Asian Journal of Chemistry, 2010)
The medicinal applications in various parts of Syzygium cumini viz., antiglycemic, antibacterial and antiinflammatory have been pharmacologically tested. An attempt has been made in this investigation to analyze the seed constituents to possibly give an insight into the constituents that could play a vital role in the medicinal activity. This work is of interest from the fact that the seeds are thrown out as waste. Chemito Model GC-8610 was used to analyze the composition of seed extract for their fatty acid content. It was observed that the percentage of oleic acid was the highest, followed by linoleic. A maximum of 46 components was observed on analysis. However, only about 10-12 components came out to be the major constituents. These studies would be continued further to explore and identify the other constituents for their importance in medicine.